Interpreters in the Courtroom: the Importance of Competence and Quality - Kościałkowska-Okońska, Ewa (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2010)
Court interpreting is becoming an increasingly important issue in Translation Studies and interpreting research. The article will be devoted to the analysis of the concepts of competence and quality and their manifestation in the court interpreter‘s work. It is assumed that the interpreter‘s competence is accomplished in three basic fields, i.e., linguistic (embracing the perfect command of the mother tongue and the foreign language), cultural (knowledge on two cultural realities) and cognitive (combining such cognitive factors as intelligence, experience, general knowledge or motivation). Quality is the concept in interpreting closely related with successful performance and communication (with all its aspects). The attempt at quality description, apart from subjective impressions resulting from our understanding of the importance of features that good – competent – translation and effective communication should have, cannot be devoid of focusing on three principal factors, i.e., the interpreter (as the text author/ producer), interpreting process and product, which is the result of this process and involvement (and competence) on the part of the interpreter. All the above aspects pose a real challenge for the court interpreter.

Tłumaczenie sądowe (ustne) staje się coraz istotniejsze w badaniach nad przekładem w ogóle i tłumaczeniem ustnym w szczególności. Artykuł poświęcony jest analizie takich pojęć jak kompetencja i jakość oraz ich realizacja w pracy tłumacza sądowego (przysięgłego). Przyjęto założenie, że kompetencja tłumacza jest realizowana w trzech głównych domenach, a mianowicie językowej (obejmującej doskonałą znajomość języka obcego i ojczystego), kulturowej (wiedza dotycząca dwóch rzeczywistości językowych) oraz kognitywnej (łączącej takie czynniki poznawcze jak inteligencja, doświadczenie, wiedza ogólna czy motywacja). Pojęcie jakości w przekładzie ustnym jest ściśle związane z dobrym tłumaczeniem i skuteczną komunikacją. Próba opisu jakości powinna również koncentrować się na trzech głównych filarach tłumaczenia, a zatem na tłumaczu (jako autorze/twórcy tekstu), procesie tłumaczeniowym i jego produkcie z tego procesu wynikającym oraz zaangażowaniu i kompetencji tłumacza. Powyższe aspekty stanowią prawdziwe wyzwanie dla tłumacza sądowego (przysięgłego).
Wpływ umiejętności tłumacza sądowego na jakość przekładu